Synthesis of Glyoxalic Acid Using Methyl Dichloroacetate by Microwave Method - Niu, Qian; Luo, Xiong; Li, Shou-Gao; Meng, Ying; Li, Fu-Xiang (Asian Journal of Chemistry, 2014)
Microwave irradiation was used to synthesize glyoxalic acid from methyl dichloroacetate. The effects of the irradiation time, reaction temperature, reactant ratio and different alkali on the yield of glyoxalic acid were studied and also compared with those effects under conventional heating. The yield of glyoxalic acid can reach 84.6 % within 6 h under the microwave irradiation, which is 12.2 % higher than that under conventional heating within 12 h. The optimum reaction time is 7.5 h and the optimum reaction temperature is 75 °C under the microwave irradiation. The results indicated that microwave irradiation was superior to the conventional heating obviously.